2016
DOI: 10.1016/j.bbrc.2016.04.060
|View full text |Cite
|
Sign up to set email alerts
|

12-oxo-phytodienoic acid, a plant-derived oxylipin, attenuates lipopolysaccharide-induced inflammation in microglia

Abstract: Jasmonates are plant lipid-derived oxylipins that act as key signaling compounds in plant immunity, germination, and development. Although some physiological activities of natural jasmonates in mammalian cells have been investigated, their anti-inflammatory actions in mammalian cells remain unclear. Here, we investigated whether jasmonates protect mouse microglial MG5 cells against lipopolysaccharide (LPS)-induced inflammation. Among the jasmonates tested, only 12-oxo-phytodienoic acid (OPDA) suppressed LPS-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…LPS leads to glial activation, that is astrocytosis and reactive microglia, which releases inflammatory cytokines such as TNF-α and IL-1β. These inflammatory mediators are involved in various neurodegenerative disorders such as Alzheimer’s disease, Parkinson’s disease, multiple sclerosis, and cerebral ischemia [52,53,54]. Herein, we observed that LPS markedly elevated microglial activation and astrocytosis by enhancing the TLR4 receptor expression, but hesperetin ameliorated the reactive gliosis and astrocytosis by downregulating the TLR4-mediated GFAP and Iba-1 expression.…”
Section: Discussionmentioning
confidence: 85%
“…LPS leads to glial activation, that is astrocytosis and reactive microglia, which releases inflammatory cytokines such as TNF-α and IL-1β. These inflammatory mediators are involved in various neurodegenerative disorders such as Alzheimer’s disease, Parkinson’s disease, multiple sclerosis, and cerebral ischemia [52,53,54]. Herein, we observed that LPS markedly elevated microglial activation and astrocytosis by enhancing the TLR4 receptor expression, but hesperetin ameliorated the reactive gliosis and astrocytosis by downregulating the TLR4-mediated GFAP and Iba-1 expression.…”
Section: Discussionmentioning
confidence: 85%
“…proved that the compound was (9 S ,13 R )-12-OPDA, i.e., (+)- trans -12-OPDA [40]. Except for the activity as a plant hormone, 12-OPDA exerted cytoprotective effects in human neuroblastoma SH-SY5Y cells subjected to oxidative stress [41], mitigated LPS-induced inflammation in microglia [42], inhibited proliferation of human breast cancer cells [43], and demonstrated antileishmanial activity [44]. Thus, we decided to check whether or not the compound may contribute to the overall activity of C. divaricatum .…”
Section: Discussionmentioning
confidence: 99%
“…The effects of JA‐related oxylipins on mammals have attracted much attention because of their structural similarities to mammalian oxylipins such as prostaglandins and leukotrienes. Known in vitro and in vivo effects of JA‐related oxylipins include anti‐inflammatory and anti‐cancer effects, and anti‐ageing properties on human skin 29,30 . Therefore, the seed coat of developing G. max seeds may be a promising source of these JA‐related oxylipins.…”
Section: Resultsmentioning
confidence: 99%
“…Known in vitro and in vivo effects of JA-related oxylipins include anti-inflammatory and anti-cancer effects, and anti-ageing properties on human skin. 29,30 Therefore, the seed coat of developing G. max seeds may be a promising source of these JA-related oxylipins. Pharmacokinetic analyses (i.e., post-consumption tissue-localisation analyses of phytochemicals) have been conducted using MALDI-MSI.…”
Section: Quantification Of αLamentioning
confidence: 99%